ANALISIS SISTEM ANTRIAN LAYANAN TELLER PADA BANK BRI KCP JAKENAN PATI - Setyawan, Agung Slamet; Sudaryanto, Budi (Faculty of Economics and Business Diponegoro University, 2016)
The main problem that occurs in Bank BRI KCP Jakenan Pati still long waiting time for the customer for the system enters the service queue to get their turn. This study aims to determine the waiting time on average per customer, the number of tellers are optimized so that bank customers are not the queue is too long, timeliness of service queuing model that is being implemented at Bank BRI KCP Jakenan Pati with the standard of service Bank of time and a model of a queuing system other can reduce customer wait time in getting services to improve the effectiveness of service time. The object of this study is that the banking company Bank BRI KCP Jakenan Pati. The population used in this study is the total number of customer arrival in January 2016 came at 8: 00-14: 00 every Monday, Tuesday and Friday in one month so that the data can be expected to be taken within 12 working days. Methods of data analysis using Multi-Channel Single Phase. Based on the research results, in the crowded conditions of the average waiting time in the queue was 59 minutes. Under normal conditions the average waiting time in the queue is 6 minutes. In calm conditions the average waiting time in the queue is 1 minute 30 seconds. Modeling queuing system that can optimize teller level of usability and minimize customer wait time is by adding a second teller to teller during crowded conditions and normal and remained at 1 teller during calm conditions. So that the queuing system at Bank BRI KCP Jakenan Pati changed from using the queuing system Single-Channel Single Phase into a queuing system Multi-Channel Single Phase to increase the number of servers / teller.